Electrocardiographic Parameters as Predictors of Response to Cardiac Resynchronization Therapy - Poposka, Lidija; Boskov, Vladimir; Risteski, Dejan; Jane Taleski; Janusevski, Filip; Srbinovska, Elizabeta; Georgievska-Ismail, Ljubica (ID Design 2012/DOOEL Skopje, 2018)
INTRODUCTION: Although strict selection criteria are used to select patients for cardiac resynchronisation therapy, up to 30% of patients do not have a positive clinical response. PATIENTS: A total of 102 consecutive patients who had biventricular pacemaker/defibrillator (CRT-P or CRT-D) implanted were enrolled in this prospective observational study. RESULTS: During the average follow-up period of 24.3 months 5 patients died and 17 (16.7%) patients were hospitalised with the symptoms of heart failure; 75 (73.5%) patients were responders based on the previously defined criteria. Responders in the group of LBBB patients kept the significant difference in a computed variable (S1 + R6) - (S6 + R1) and R6/S6 ratio. Responders in non-LBBB patients kept the significant difference only in the height of R waves in V6. The R6/S6 ratio tended to be higher, but it did not reach a statistical significance. CONCLUSION: None of the tested ECG parameters stands out as an independent predictor of response to cardiac resynchronisation therapy, but some of them were different in responder-compared to the non-responder group. The amplitude of R wave in V6, higher R/S ratio in V6 and higher computed variable (S1 + R6) - (S6 + R1) may predict the likelihood of response to CRT therapy in both LBBB-patients and non-LBBB patients.
Keywords: Cardiac resynchronization therapy; Responders; non-responders; non-LBBB; Electrocardiography parameters